A rare case of exomphalos with an umbilical cord teratoma. (18th April 2012) - Shawkat, E; Keene, DJB; Gillham, J; Craigie, RJ
Abstract : A healthy 34-year-old para 1 had a normal booking scan. At 20 weeks gestation, on the anomaly scan, a well-defined echogenic area was identified within the cord, adjacent to which was a cyst. All other anatomy was normal. She was referred to the Fetal Management Unit (FMU) at Saint Mary's Hospital (SMH) for more detailed scanning. A scan performed at the FMU showed a small cord hernia that measured 1.2cm at the base and contained bowel. The working diagnosis was exomphalos minor. The patient was counselled about the risks of associated chromosomal abnormalities and genetic syndromes. Invasive testing for karyotype was offered but declined. Further growth scans revealed slight enlargement of the hernia but growth and liquor volume remained normal. At 38+5 weeks she was induced and had a normal vaginal delivery of a baby girl that weighed 3763g. At delivery, an exomphalos was found in association with a large solid mass. Surgery was performed to repair the exomphalos and resect the mass that was attached to a segment of normal small bowel. Histopathological examination revealed an umbilical cord teratoma. The infant was alive and well at 6 months of age. Congenital teratomas of the umbilical cord are extremely rare with 14 cases reported in the literature. Four cases in humans involve the combination of an umbilical cord teratoma and exomphalos. Two of these cases were terminated. We report the second fetus to be delivered normally, remaining alive and well following resection of the teratoma and repair of the exomphalos.